Are we all Amazon Primed? Consumers and the politics of platform power - Culpepper, P; Thelen, K (SAGE Publications, 2019)
This article articulates a distinctive source of political influence of some technology firms, which we call platform power. Platform power inheres in companies of economic scale that provide the terms of access through which large numbers of consumers access goods, services, and information. Firms with platform power benefit from a deference from policymakers, but this deference is not primarily a function of direct influence through lobbying or campaign contributions, nor does it come from the threat of disinvestment. Companies with platform power instead benefit from the tacit allegiance of consumers, who can prove a formidable source of opposition to regulations that threaten these platforms. Focusing on the critical role played by consumers in explaining the powers platform firms wield in the rich democracies lends insight as well into their distinctive vulnerabilities, which flow from events that split the consumer–platform alliance or that cue citizen, as opposed to consumer, political identities.